Cigarette Smoking Effect on Microhardness and Flexural Properties of Denture Base Resins - Atf Ghariani; Sabra Jaâfoura; Sana Bekri; Amel Labidi; Mounir Trabelsi (Association of Support to Oral Health Research (APESB), 2023)
Objective: To identify the tobacco effect on flexural properties and the microhardness of three acrylic resins. Material and Methods: Three resins were tested: two thermo-polymerizable acrylic resins (RMB 20 and BMS 014) and one autopolymerized acrylic resin. The 3-point bending and microhardness tests were carried out with a universal tensile-compression machine and a micro-Vickers hardness tester. The acrylic resin specimens have been exposed for 21 days to cigarette smoke in a smoking room. Their mechanical strength was compared to unexposed samples. Statistical analysis was performed using the data processing software SPSS Statistics 21.0. Results: The flexural properties of the resins were affected by cigarette smoke only in the case of Major Base 20® (drop in strength with p= 0.02; 0.6; 0.7 and in elastic modulus with p= 0.86; 0.74 and 0.85 for Major Base 20®, BMS 014® and Major Repair®). The cigarette smoke affected significantly microhardness for all groups (p<0.001). Conclusion: Cigarette smoking does not affect the flexural properties of the acrylic resin (BMS 014® and Major Repair® unlike Major Base 20®), but it does reduce the microhardness.